Electron transfer and H2 evolution in hybrid systems based on [FeFe]-hydrogenase anchored on modified TiO2. (6th July 2016) - Polliotto, Valeria; Morra, Simone; Livraghi, Stefano; Valetti, Francesca; Gilardi, Gianfranco; Giamello, Elio
Abstract: The hybrid systems composed by [FeFe]-hydrogenase anchored to the surface of three distinct types of TiO2 (anatase) have been investigated using Electron Paramagnetic Resonance (EPR) spectroscopy in dark and under illumination. The three supports were bare TiO2, nitrogen doped TiO2 (N-TiO2 ) and a sub-stoichiometric form of the same oxide (TiO2−x ) exhibiting blue color. EPR spectroscopy has shown that the electrons photogenerated by irradiation of the supports are stabilised by the solid forming Ti 3+ paramagnetic ions while, in the case of the hybrid systems electrons are scavenged by the anchored protein becoming available for H + reduction. The ability of the three hybrid systems in hydrogen production under solar light illumination has been compared. The formation of H2 is higher for the system containing N-TiO2 (yellow) with respect to that based on the bare oxide (white) indicating that the visible light absorbed, due to the presence of N states, is actually exploited for hydrogen production. The system containing reduced blue TiO2, in spite of its deep coloration, is less active suggesting that a specific type of visible light absorption is needed to produce photoexcited electrons capable to interact with the anchored protein. Graphical abstract: Highlights: The effect of irradiation of hydrogenase-TiO2 hybrid systems has been monitored. Bare TiO2, N-TiO2 and substoichiometric TiO2 have been tested as supports. An electron transfer from oxide to protein occurred under irradiation. Hydrogenase- N-TiO2 hybrid system has given the highest values of H2 production.